2015
DOI: 10.4103/0377-4929.151203
|View full text |Cite
|
Sign up to set email alerts
|

High-grade myxofibrosarcoma-presented as a large mass of right upper arm

Abstract: Myxofibrosarcoma is one of the rare soft tissue sarcomas. We present a case of a 65-year-old male having large soft tissue mass over right upper arm associated with surface ulceration. On histopathological study tumor was diagnosed as myxofibrosarcoma - high grade according to modified FNCLCC grading system. Like many other tumors of connective tissue, soft tissue sarcoma exhibits high recurrence. In our case, tumor showed features of high grade with local recurrence, large size; however, no evidence of metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…The differential diagnosis with giant cells are osteosarcoma, fibrosarcoma, high-grade myxofibrosarcoma, leiomyosarcoma and undifferentiated high-grade pleomorphic sarcoma. 10,11 Secondary malignancy in giant cell tumor of bone has a poor prognosis .In various studies it was observed that the prognosis was better in patients with primary malignancy in giant cell tumor of bone than secondary malignancy. As there is lack of long-term follow-up data on the prognosis of malignant GCTB is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis with giant cells are osteosarcoma, fibrosarcoma, high-grade myxofibrosarcoma, leiomyosarcoma and undifferentiated high-grade pleomorphic sarcoma. 10,11 Secondary malignancy in giant cell tumor of bone has a poor prognosis .In various studies it was observed that the prognosis was better in patients with primary malignancy in giant cell tumor of bone than secondary malignancy. As there is lack of long-term follow-up data on the prognosis of malignant GCTB is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The differential diagnosis are myxoma, low grade liposarcoma, myxofibrosarcoma, angiomyxofibroma, fibroepithelial stromal polyp, myxoid neurofibroma etc. 7,8 Angiomyxomas are usually <5 cm with well circumscribed lesions and have rounded or epithelial cell clusters with alternating hypercellular areas. While aggressive angiomyxomas are larger >5 cm, not circumscribed and hypocellular with spindle or stellate cells with infiltrating margins.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are located in extremities. 8 Immunohistochemical study for vimentin, S-100, Desmin, CD34, ER, PR, SMA etc. have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence is observed in between 50 and 60% of the cases, regardless of the histologic grade. 3 4 5 6 The aim of the present study was to describe the surgical reconstruction in a case of extensive myxofibrosarcoma in the upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…A recorrência local ocorre em 50-60% dos casos, independentemente do grau histológico. 3 4 5 6 O objetivo deste trabalho foi descrever a reconstrução cirúrgica em um caso de extenso mixofibrossarcoma no membro superior.…”
Section: Introductionunclassified